2019
DOI: 10.1194/jlr.m090373
|View full text |Cite|
|
Sign up to set email alerts
|

Docosahexaenoic acid is both a product of and a precursor to tetracosahexaenoic acid in the rat

Abstract: Tetracosahexaenoic acid (THA; 24:6n-3) was first reported to be the immediate precursor to DHA in 1991 by Voss et al. (1), where n-3 docosapentaenoic acid (DPAn-3; 22:5n-3) had previously been thought to be directly converted to DHA via a 4-desaturation reaction. Later, a lack of labeled DHA accumulation in Zellweger's patients (2, 3) signaled a role for the peroxisomes in the -oxidation of THA to DHA, following the elongation and subsequent 6desaturation of DPAn-3 to n-3 tetracosapentaenoic acid (TPAn-3; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
(47 reference statements)
2
15
0
Order By: Relevance
“…Regardless of the type of cancer considered, hormone-dependent or not, the youngest patients exhibited the most proliferative tumors, in agreement with the data in the literature. The % expression of Ki-67 allows researchers to define the proliferation index of the tumors [25], and its use in BC with a cut-off varying according to the authors from 1% to 28% [26]. In order to overcome the lack of consensus concerning this cut-off, we differentiated Ki-67 ≤ 20% as Prolif− and Ki-67 ≥ 30% as Prolif+.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the type of cancer considered, hormone-dependent or not, the youngest patients exhibited the most proliferative tumors, in agreement with the data in the literature. The % expression of Ki-67 allows researchers to define the proliferation index of the tumors [25], and its use in BC with a cut-off varying according to the authors from 1% to 28% [26]. In order to overcome the lack of consensus concerning this cut-off, we differentiated Ki-67 ≤ 20% as Prolif− and Ki-67 ≥ 30% as Prolif+.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have indicated that the increase in EPA is not associated with retroconversion, but to inhibition of further transformation of EPA to DPA(-DHA) [44,45]. Results from a study in rats even suggest a transformation of DHA to THA [46]. In our study we did not detect THA, not even at the highest provided doses, suggesting that retroconversion [47] and/or feedback inhibition of EPA metabolism was predominating, explaining the unchanged DPA in the lower doses [48].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may be designed using intracerebroventricular injections of THEA to determine the half-life in the brain compared with other NAEs, such as DHEA. Alternatively, THA is rapidly converted to DHA in vivo (23), and if THEA synthesis is saturated, the excess unesterified THA in the brain could be used to synthesize additional DHA, and in turn DHEA. These are important molecules in neuroinflammation, as both unesterified DHA (40) and DHEA (41) are protective against lipopolysaccharide-induced neuroinflammation in rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the blood and other tissues, the brain has some of the highest levels of THA in the body (23,(25)(26)(27), and may therefore have added importance in neural tissues. In our animals, total brain THA was at least 20 nmol/g across all conditions and is substantially higher than previous reports of 1-6 nmol/ml THA in rodent plasma (23,26) and 1-3 nmol/ml in human plasma (42). This enrichment Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation